Improving the Students’ English Competence Through Grammar Translation Method on the Second Semester of J Class at STAIN Jember in 2010/2011 Academic Year - Suparwoto Sapto Wahono (Fenomena, 2011)
The English course at STAIN Jember is a compulsory subject that must be taken by students. One of the objectives of learning English is to understand English literature to support students' final assignments. Some obstacles faced by students in understanding literature include their lack of vocabulary mastery. Additionally, students have limited understanding of sentence structure. These two shortcomings result in students' inability to comprehend reading texts effectively. Therefore, the grammar translation method was implemented to enhance students' English competence. Mata kuliah Bahasa Inggris di STAIN Jember merupakan mata kuliah wajib yang harus ditempuh oleh mahasiswa. Salah satu tujuan dari pembelajaran bahasa Inggris adalah untuk memahami literatur bahasa Inggris dalam rangka mendukung tugas akhir mahasiswa. Beberapa kendala yang dialami mahasiswa untuk memahami literatur adalah kurangnya penguasaan kosakata yang dimiliki mahasiswa. Di samping itu, penguasaan struktur kalimat kurang dipahami oleh mahasiswa. Dari dua penguasaan itu, mahasiswa menjadi kurang mampu memahami bacaan teks. Oleh karena itu, metode grammar translation diterapkan untuk meningkatkan kemampuan bahasa Inggris mahasiswa.